Pengaruh Likuiditas, Profitabilitas, dan Leverage Terhadap Perubahan Laba Pada Perusahaan Manufaktur Subsektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017 - Friska Darnawati; Yohana Ayu Siagian; Fitra Ginting; Yusrina Siahaan; Cincin Marintan Pasaribu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The study carried out in the working of this journal aims to understand how big and important the performance of financial ratios, among which is liquidity calculated by the current ratio, profitability calculated by return on assets, leverage is calculated by the debt to asset ratio to earnings changes. The numbers of samples in this study were 12 companies with 4 years of research and being filtered by using purposive sampling techniques. Data were analyzed using the classic assumption test model, multiple linear tests, coefficient of determination, partial ( t ) and simultaneous ( f ). Data processing using SPSS 25. The study results prove that liquidity, profitability and leverage are able to explain its existence simultaneously with variables change in profit. In addition, the current ratio ( CR ) and debt to asset ratio partially have a positive and significant effect on earnings changes, while in the ratio of return on asset ( ROA ) is not significant and has no effect on earnings changes